Effect of defibrillator on long term all-cause mortality in patients with chronic kidney disease: an updated meta-analysis. (3rd October 2022) - Aslam, F; Al-Sadawi, M; Aleem, S; Alsaiqali, M; Almasry, I; Singh, A; Rashba, E; Fan, R
Abstract: Background: The beneficial role of implantable defibrillator (ICD) in patients with chronic kidney disease (CKD) is less understood as this population is often not well represented in clinical trials. Purpose: Evaluate the effect of ICD use in patients with CKD on long term outcomes. Methods: Literature search was conducted for studies reporting the effect of ICD on all-cause mortality in patients with CKD, which is defined as glomerular filtration rate (GFR) <60 mL/min. The search was not restricted to time or publication status. The search included the following databases: Ovid MEDLINE, EMBASE, Scopus, Web of Science, Google Scholar, and EBSCO CINAHL. The minimum duration of follow-up required for inclusion was one year. Results: The literature search identified 834 studies, of which 14 studies with 70, 661 patients were included. Mean follow up was 39 months (12–81 months). For all patients with CKD, ICD was associated with lower all-cause mortality (log HR −0.247, SE 0.101, p=0.015); Heterogeneity: df=13 (P<0.01), I 2 =97.057; Test for overall effect: Z=−2.431 (Figure 1). When further stratified based on dialysis, CKD patients without the need for dialysis had favorable outcome (log HR −0.211, SE 0.095, p=0.026); Heterogeneity: df=6 (P<0.01), I 2 =70.146; Test for overall effect: Z=−2.225, whereas ICD implantation in CKD patients requiring dialysis was not associated with mortality benefit (log HR −0.262, SE 0.134, p=0.051) (Figure 2A, B). Conclusion: ICD implantation is associated with mortality benefit in patients with CKD, but this association is not present for patients requiring dialysis. Funding Acknowledgement: Type of funding sources: None.